The Influence of Organizational Commitment and Transformational Leadership on Performance through Employee Job Satisfaction of PT Angkasaraya Nusantara - Mulyawan, Agus; Suharto; Samosir, Partogi Saoloan (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
In the results of this research, statistically the coefficient states that partially the contribution of transformational leadership has a positive but not significant influence on employee performance, while organizational commitment has a positive and significant influence on employee performance. However, if both simultaneously have a significant influence on employee performance. Furthermore, the contribution of organizational commitment and transformational leadership to employee performance both have a positive and significant influence, both partially and simultaneously. The contribution of job satisfaction to employee performance has a positive and significant influence. Furthermore, in the analysis of organizational commitment and transformational leadership on employee performance through job satisfaction, it was found that there was no mediating effect of job satisfaction in the relationship between organizational commitment and employee performance, but a mediating effect of job satisfaction was found in the relationship between transformational leadership and employee performance.